2020
DOI: 10.3892/etm.2020.8469
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic comparison of gut microbiota of mice infected with Shigella�flexneri via two different infective routes

Abstract: Shigella is one of the main pathogens causing diarrheal disease, and is associated with high morbidity and mortality in developing countries. Previous clinical data and animal studies have shown that the outcomes of oral and peritoneal infections of Shigella differ, and that the latter is more serious. Furthermore, a variety of pathogenic bacteria are known to cause changes in intestinal flora after infection, and the influence of Shigella infection on intestinal flora remains poorly understood. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…We observed that the relative abundances of Faecalitalea, Sphingomonas, Sutterella and Mycobacterium were significantly higher in CAs group. Faecalitalea is a probiotic that could use D-glucose, sucrose, D-mannose, and raffinose as a substrate to produce butyric acid (Ma et al, 2020;Yang et al, 2020). It has been revealed to have beneficial effects on energy supply for epithelial growth, improving the intestinal flora and inhibiting inflammation, reinforcing various components of the mucosal barrier and reducing oxidative stress in the intestine (Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the relative abundances of Faecalitalea, Sphingomonas, Sutterella and Mycobacterium were significantly higher in CAs group. Faecalitalea is a probiotic that could use D-glucose, sucrose, D-mannose, and raffinose as a substrate to produce butyric acid (Ma et al, 2020;Yang et al, 2020). It has been revealed to have beneficial effects on energy supply for epithelial growth, improving the intestinal flora and inhibiting inflammation, reinforcing various components of the mucosal barrier and reducing oxidative stress in the intestine (Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, 7% were infected with Shigella bacteria (Zhu et al, 2016), and in Ghana, there were 5.60% positive Shigella from 347 samples examined (Ashie et al, 2017). Shigella is a gram-negative bacteria whose habitat is in the digestive tract with infection through the oral phase (Yang, Chen, Xia, & Zhang, 2020). Shigella can cause infection in all age groups.…”
Section: Discussionmentioning
confidence: 99%
“…According to Zhang et al [ 58 ], increasing the SCFA-producing genera Blautia and Allobaculum could enhance intestinal integrity and reduce the body weight in obese mice[ 59 ], thus rivaling obesity. Allobaculum is a member of Lachnospiraceae , Ruminococcaceae , and Erysipelotrichaceae , a family that affects host metabolism[ 60 ] and protects body weight gain from HFD. Allobaculum can produce butyric acid and propionic acid[ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%